Targeting the Mevalonate Pathway Enhances the Efficacy of Epidermal Growth Factor Receptor – Tyrosine Kinase Inhibitors in Head and Neck Squamous Cell Carcinoma - Mukhtar, Lenah (Université d'Ottawa / University of Ottawa, 2020)
Epidermal growth factor receptor (EGFR) is highly expressed in head and neck squamous cell carcinoma (HNSCC) and non-small cell lung cancer (NSCLC) and is a key regulator of tumor cell growth and survival. Erlotinib, also known as tarceva, (a first-generation) and afatinib, also known as giotrif, (a second-generation) are tyrosine kinase inhibitors (TKIs) of EGFR. These TKIs are recognized therapeutic agents in these tumor types, as they inhibit EGFR signaling but show limited activity as single agents. Novel strategies will likely require EGFR-TKIs combination with an agent(s) that will enhance their therapeutic efficacy. Recently, we have demonstrated that combining statins, inhibitors of the mevalonate pathway, with erlotinib enhanced EGFR inhibition and induced synergistic cytotoxicity through the activation of cellular integrated stress response pathway (ISR) regulated by the induction of activating transcription factor 3 (ATF3). In our Phase I clinical trial, combining rosuvastatin with erlotinib, while demonstrating clinical activity, this treatment also showed statin-induced myopathies likely the result of diminished ubiquinone levels, which limited their utilization. Therefore, alternative strategies are warranted. Targeting geranylgeranyl diphosphate (GGPP) synthesis or its incorporation, a downstream mevalonate metabolite, represents such an approach with the potential to circumvent statin-associated toxicities but retain the efficacy in combination with EGFR inhibitors. In this project, we evaluated the effect of the combination of geranylgeranyl transferase-I inhibitor (GGTI-298) with the EGFR inhibitor, tarceva, (aim 1) and a GGPP synthase inhibitor, digeranyl bisphosphonate (DGBP), with the EGFR inhibitor, afatinib, (aim 2). For aim 1, we demonstrated that GGTI-298 treatment induced ATF3 expression in SCC9 and SCC25 cells and in a cohort of ex-vivo tumor tissues. Furthermore, GGTI-298 and tarceva induced synergistic cytotoxicity in SCC cells that was dependent on ATF3 expression, as ATF3 deficient murine embryonic fibroblasts (ATF3-/- MEFs) displayed attenuated cytotoxicity in response to GGTI-298 alone and in combination with tarceva. Similarly, SCC9 sub-lines that were selected as resistant to GGTI-298 through prolonged exposure to this agent also failed to demonstrate synergy with treatment of GGTI-298 in combination with tarceva. For aim 2, we demonstrated that the specific GGPP synthase inhibitor, DGBP, induced cytotoxicity in SCC cells. We further demonstrated this specificity as specific shRNA targeting of GGPP synthase as well as the inhibitor DGBP significantly enhanced the cytotoxic activity of the EGFR-TKI afatinib in SCC cells. DGBP as well as afatinib treatments induced ATF3 expression in SCC cells in vitro and in a cohort of ex-vivo tumor tissues. Co-administration of the downstream metabolite GGPP inhibits the induction of ATF3 and the cytotoxic and apoptotic effects associated with DGBP treatment. Furthermore, the synergistic cytotoxicity induced by the combination of DGBP and afatinib in SCC cells was also dependent on the expression of ATF3 through the induction of cellular stress response pathways. Taken together, these results suggest the potential clinical utility of combining downstream mevalonate inhibitors (GGTI-298 or DGBP) with EGFR inhibitors in HNSCC patients as a novel and more refined combination therapeutic approach.
Keywords: HNSCC; GGDPS; GGTI; GGPP; ATF3; DGBP